Existence and uniqueness theorem to a unimolecular heterogeneous catalytic reaction model - Ambrazevičius, A. (Nonlinear Analysis: Modelling and Control, 2010)
A mathematical model for an unimolecular heterogeneous catalytic reaction is considered in the case when the reaction product slowly desorb and then diffuse away from the surface. This model is described by a coupled system of nonlinear parabolic and two ordinary differential equations. The existence and uniqueness theorems of classical solution are proved for this system.